Nutrition-related knowledge, attitudes, practice, and mental health status of people living with HIV in Dubai, United Arab Emirates: A cross-sectional descriptive study - Souheir M. Alia; Taoufik L. Zoubeidi; Habiba I. Ali (PLoS ONE, 2026)
Background Despite significant advancements in management, Human Immunodeficiency Virus (HIV) infection remains a global health concern. Limited research exists on the nutrition-related knowledge, attitudes, and practices (KAP) of people living with HIV (PLHIV) in the Middle East. This study assessed nutrition-related KAP and mental health status among PLHIV attending an HIV management clinic in Dubai, United Arab Emirates (UAE). Methods A cross-sectional study was used to assess HIV/AIDS nutrition-related KAP. The total KAP scores ranged from 13–69, with scores between 13–32 representing poor, 33–51 average, and 52–69 good KAP. The Hospital Anxiety and Depression Scale (HADS) was used to screen the patients for anxiety and depression. Data was collected face-to-face from August to November 2023. Results Data were collected from 63 patients attending an outpatient clinic. The mean age of the participants was 40 ± 12.4 years, and 80% were men. Most participants (87.3%) demonstrated good KAP (84.6%% and 89.8% for females and males, respectively). Mental health screening for depression and anxiety showed mean total scores of 4.73 ± 3.6 and 4.9 ± 4.9, respectively, which correspond to normal levels. The prevalence of abnormal HADS depression and HADS Anxiety were 8.0% and 17.%, respectively. Conclusions This study found that the participants had good nutrition-related KAP scores, with the prevalence of depression and anxiety less than 20% which is significantly lower than estimates for PLHIV worldwide. This is the first study to explore KAP and mental health status among PLHIV in the Arabian Gulf region.